2016
DOI: 10.5139/ijass.2016.17.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithm-based scheduling for ground support of multiple satellites and antennae considering operation modes

Abstract: Given the unpredictability of the space environment, satellite communications are manually performed by exchanging telecommands and telemetry. Ground support for orbiting satellites is given only during limited periods of ground antenna visibility, which can result in conflicts when multiple satellites are present. This problem can be regarded as a scheduling problem of allocating antenna support (task) to limited visibility (resource). To mitigate unforeseen errors and costs associated with manual scheduling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…These approaches have been tailored to suit different satellite configurations, including both agile [13] and non-agile types [14], as well as to interact with ground stations [15]. In addition to MILP-based studies, meta-heuristic methods like Genetic Algorithms (GA) [16][17][18], Ant Colony Optimization (ACO) [19], and Particle Swarm Optimization (PSO) [20] have gained traction for complex scenarios, especially those requiring rapid response, such as natural disasters [21]. With the rise of Artificial Intelligence (AI), the field has seen a paradigm shift towards utilizing machine learning algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches have been tailored to suit different satellite configurations, including both agile [13] and non-agile types [14], as well as to interact with ground stations [15]. In addition to MILP-based studies, meta-heuristic methods like Genetic Algorithms (GA) [16][17][18], Ant Colony Optimization (ACO) [19], and Particle Swarm Optimization (PSO) [20] have gained traction for complex scenarios, especially those requiring rapid response, such as natural disasters [21]. With the rise of Artificial Intelligence (AI), the field has seen a paradigm shift towards utilizing machine learning algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is a relative scarcity of research focused on satellite constellations, aligning with the recent trend in satellite development. Additionally, the current body of work often relies on widely used meta-heuristic algorithms [16][17][18][19][20][21] for mission planning optimization. These algorithms, while effective in certain scenarios, tend to fall into local optima and lack consistency in producing identical results in each iteration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Equations ( 9)-( 18) are constraints on generating the schedule path of a satellite. Constraint (9) ensures the continuity of a schedule path, and Constraint (10) means that the schedule path cannot stay at a node (i, p). Constraints ( 11) and (12) indicate that a node cannot be connected with multiple nodes simultaneously.…”
Section: ∈𝐏 ∈𝐔mentioning
confidence: 99%
“…Xhafa et al [8] have suggested a GA for ground-station allocation problems to maximize the number of communications, communication time, and communication ground stations and minimize the number of communication collisions between satellites. When the visibilities of satellites conflict with the same ground station, Lee et al [9] and Lee et al [10] have introduced a GA with a greedy method that can select a satellite while considering various factors such as priority, urgency, and profit. Luo et al [11] have suggested a heuristic algorithm combining a pre-scheduling strategy that places high-profit schedules first and a rescheduling strategy that coordinates arranged and non-placed schedules.…”
Section: Introductionmentioning
confidence: 99%
“…A genetic algorithm (GA) is another alternative to deal with complex problems such as task scheduling. There is plenty of satellite task scheduling research based on genetic algorithms [25,26]. Mixed-Integer Linear Programming (MILP) is also another approach to making satellite task schedules [27][28][29].…”
Section: Autonomous Task Schedulingmentioning
confidence: 99%